Hydrological Analysis for Water Resources Conservation in the Design of Bandungrejo Lake, Indonesia - Brontowiyono, Widodo (Budapest International Research and Critics University, 2021)
An artificial lake design for water resource conservation requires a hydrological analysis that must be comprehensive and detailed to be successful. . This study aims to analyze the maximum rainfall frequency, synthetic unit hydrographs (SUH), design rainfall hyetographs, adequate rainfall, design flood discharge, and lake conservation concepts. The Chi-Square and Kolmogorov-Smirnov tests were used to analyze the maximum rainfall frequency, and the Nakayasu method was used for the Synthetic Unit Hydrograph analysis. The Alternating Block Method (ABM) was employed to analyze the design rainfall hyetograph, and the φ index method was employed for the practical rainfall calculation. The design flood discharge was calculated based on the comparison between the rational method and unit hydrograph. The frequency analysis in average distribution results in 168.7 mm daily rainfall for a 10-year return period, 182.5 mm for a 20-year return period, and 198 mm for a 50-year return period. The Nakayasu analysis shows that the time to peak run-off is 0.56 hours or rounded up to the nearest hour (1st hour). The study of design rainfall hyetograph for a 50-year return period shows 109.0 mm maximum rainfall intensity at the 3rd hour. The adequate rainfall analysis results in 98.5 mm maximum effective rainfall at the 3rd hour. Meanwhile, the Nakayasu method for Synthetic Unit Hydrograph (SUH) obtains 16.68 m3/s design flood discharge for 50 years.